Analysis on the effect of dielectric material and copper thickness of substrate towards the performance of ultra wideband ground slotted T-shaped power divider - Yusof, Khairul Huda (Penerbit UTM Press, 2015)
Nowadays, the fifth generation (5G) wireless system is extensively studied to fulfill the continuously increasing demand for high data rate and mobility in wireless communication applications. Thus, to cope with this demand, various researches are required for front-end microwave components, which includes power divider. Therefore, in this article, the design and analysis of ultra wideband T-shaped power divider is presented. Two substrates are chosen in the design, which are Rogers RO4003C and TMM4 with copper thickness of 17 µm and 35 µm to analyze their effect towards ultra wideband performance of the designed power divider. The design and analysis are performed by using CST Microwave Studio. The optimal performance of the designed power divider is subjected to dielectric material and the copper thickness of the substrate. Where, the best design is obtained using TMM4 substrate that made of ceramic thermoset polymer with 35 µm copper thickness.